Integrated model of intention to adopt cloud-based m-retail application among textile cyberpreneurs - Wan Safra Diyana Wan Abdul Ghani (2019)
Nowadays, in the dynamic fashion and textile industry, business owners are required to utilize certain technology such as cloud-based m-retail application (CBMA) for their business survival. As one of the latest business trends, CBMA has become a common application to be utilised among Malaysian business owners such as textile cyberpreneurs. Nonetheless, this technology was found to be lowly adopted among Malaysian entrepreneurs although several initiatives have been introduced by the government. This study is proposed with the aim of finding motivating factors that could lead the adoption of CBMA among textile cyberpreneurs. From review of literatures, it has been identified that studies on m-retail from the perspectives of Malaysian retailers were still lacking. Besides, there are only a few studies that applied the integration approach model specifically in understanding the adoption of m-retail technology in Malaysia. The uses of only one or two theories were not sufficient while only Technology Acceptance Model (TAM) and Innovations Diffusion Theory (IDT) were previously utilised. This study introduced an integrated model that offered a comprehensive view of adoption intention based on the most important elements of an information system which are people, system and procedures. From these elements, associated technology acceptance theories, particularly Task-Technology Fit (TTF) model, Decomposed Theory of Planned Behaviour (DTPB) and Information System (IS) Success model were integrated in the proposed model. Mixed-method approach was performed in this study where quantitative phase was conducted along with the triangulation of results via qualitative method. 600 questionnaires were distributed to Malaysian textile cyberpreneurs but only 348 usable questionnaires with 58% of response rate were analysed through structural equation modelling. Research findings on the integrated model revealed that all factors of TTF and DTPB positively influence the behavioural intention of textile cyberpreneurs upon the CBMA adoption. On the other hand, one factor of IS Success model was found to be insignificant, particularly the system quality construct whereas the other two IS Success factors were found to be significant. Prior to the insignificant result of system quality, the triangulation was conducted via in-depth interviews. The ATLAS.ti outcomes discovered a contradictory result where system quality was identified to be a significant predictor with three emerging dimensions. As a final result, system quality is retained in the proposed integrated model while the model has empirically achieved the acceptable values of model fitness index through model validation. The model is expected to be referred by the government and the key players of cloud services industry in delivering the best-suited CBMA to textile cyberpreneurs. Limitations and recommendations for future study are discussed in the final section.